MOF-derived hollow β-FeOOH polyhedra anchored with α-Ni(OH)2 nanosheets as efficient electrocatalysts for oxygen evolution. (1st April 2019) - Wang, Jingyun; Li, Shumin; Lin, Rongbin; Tu, Gaomei; Wang, Jin; Li, Zhengquan
Abstract: Hollow structured electrocatalysts have many intriguing features including large surface area, abundant active sites, and facilitated mass transportation. Metal-organic frameworks (MOF) can serve as templates to derive various hollow nanoarchitectures while the synthesis of hollow polyhedral electrocatalysts is still challenging. Herein we demonstrate a facile MOF-derived method to prepare hollow FeOOH polyhedra using MIL-53(Fe) particles as sacrifice templates, and then anchor them with dispersive Ni(OH)2 nanosheets. The developed hollow FeOOH@Ni(OH)2 composite with a honeycomb surface structure exhibits obviously enhanced oxygen evolution reaction (OER) performance in comparison with either Ni(OH)2 or FeOOH, owing to their synergistic effect and unique hollow structure. The composite shows efficient OER activity with an overpotential of 310 mV@10 mA cm −2 and a Tafel slope of 70 mV dec −1 . The formation mechanism of hollow FeOOH@Ni(OH)2 composite have been proposed and their electrochemical properties are investigated.